2015
DOI: 10.1128/jb.00309-15
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Histone-Like Protein H-NS in Motility of Escherichia coli: Multiple Regulatory Roles Rather than Direct Action at the Flagellar Motor

Abstract: A number of investigations of Escherichia coli have suggested that the DNA-binding protein H-NS, in addition to its well-known functions in chromosome organization and gene regulation, interacts directly with the flagellar motor to modulate its function. Here, in a study initially aimed at characterizing the H-NS/motor interaction further, we identify problems and limitations in the previous work that substantially weaken the case for a direct H-NS/motor interaction. Null hns mutants are immotile, largely owin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Crosslinks in that study were weaker than those reported here and may have reflected the effects of overexpression from plasmids. Subsequent work has shown that FliG is prone to non-specific interactions in glutathione S -transferase-pull-down experiments: an initially reported interaction with H-NS [39] was subsequently shown to be unlikely [47]. In experiments with FliM M as well, the present investigators have found that washes stringent enough to give reliably clean negative controls do not preserve a robust interaction with FliG.…”
Section: Discussionmentioning
confidence: 71%
“…Crosslinks in that study were weaker than those reported here and may have reflected the effects of overexpression from plasmids. Subsequent work has shown that FliG is prone to non-specific interactions in glutathione S -transferase-pull-down experiments: an initially reported interaction with H-NS [39] was subsequently shown to be unlikely [47]. In experiments with FliM M as well, the present investigators have found that washes stringent enough to give reliably clean negative controls do not preserve a robust interaction with FliG.…”
Section: Discussionmentioning
confidence: 71%
“…Our observations suggest that AbfR1 is a global acting DNA‐binding protein combining pleiotropic transcription regulation with a chromatin‐structuring role (Peeters et al ., ). This is reminiscent of H‐NS in bacteria, a DNA‐binding protein that also combines gene regulation with nucleoid organization and likewise plays a role in the regulation of motility and biofilm formation, among a wide variety of other physiological processes (Atlung and Ingmer, ; Kim and Blair, ).…”
Section: Discussionmentioning
confidence: 88%
“…Later, it was shown that this interaction increased the flagellar rotational speed and caused hypermotility (102). More-recent research, however, indicates that the H-NS effect on motility happens via an indirect and complex route (103).…”
Section: Additional Downstream Regulation Of Flagellar Genesmentioning
confidence: 99%